Polygenic risk heterogeneity among focal epilepsies. (14th October 2020) - Gramm, Marie; Leu, Costin; Pérez‐Palma, Eduardo; Ferguson, Lisa; Jehi, Lara; Daly, Mark J.; Najm, Imad M.; Busch, Robyn M.; Lal, Dennis
Abstract: Focal epilepsy (FE) is clinically highly heterogeneous. It has been shown recently that not only rare but also a subset of common genetic variants confer risk for FE. The relatively modest power of genetic studies in FE suggests a high genetic heterogeneity of FE when grouped as one disorder. We hypothesize that the clinical heterogeneity of FE is correlated with genetic heterogeneity on a common risk variant level. To test the hypothesis, we used an FE polygenic risk score "FE‐PRS" that combines small effect sizes of thousands of common variants from the largest FE‐GWAS (genome‐wide association study) into a single measure. We grouped 414 individuals with FE according to common clinical features into subgroups, either by one feature at a time or by all features combined in a cluster analysis. We examined their association with FE‐PRS compared to 20 435 matched population controls and observed heterogeneous FE‐PRS burden among the subgroups. The highest phenotypic variance explained by FE‐PRS was identified in a cluster analysis–defined FE subgroup where all individuals had unknown etiologies and psychiatric comorbidities, and the majority had early onset seizures. Our results indicate that genetic factors associated with FE have differential burden among FE subtypes. Future studies using better‐powered FE‐PRS might have clinical utility.